1984
DOI: 10.1177/002221948401701006
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Learning Styles of Adolescent Delinquents

Abstract: The association between school failure and antisocial behavior has been the focus of much discussion but little consensus. In the present study, 53 delinquent adolescents and 51 junior high school students were compared on the basis of their learning profiles. An educational battery was devised to evaluate quality of learning style and error clusters in addition to traditional grade-equivalents. Significant differences were found in the type and prevalence of multiple error clusters within each of the eight ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 11 publications
(10 reference statements)
2
24
1
Order By: Relevance
“…Of equal importance to the achievement gap between Whites and racial minorities is the distinct issue of academic disparity occurring between juvenile offenders and non-offenders (Archwamety & Katsiyannis, 2000;Beebe & Mueller, 1993, Cottle, Lee, & Heilbrun, 2001Foley, 2001;Katsiyannis, Ryan, Zhang, & Spann, 2008;Meltzer, Levine, Karniski, Palfrey, & Clarke, 1984, Zamora, 2005. For example, in a review of the academic characteristics of juvenile delinquents, Foley (2001) reported that these youth were one year to several years below expected grade levels and had high rates of academic failure and grade retention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of equal importance to the achievement gap between Whites and racial minorities is the distinct issue of academic disparity occurring between juvenile offenders and non-offenders (Archwamety & Katsiyannis, 2000;Beebe & Mueller, 1993, Cottle, Lee, & Heilbrun, 2001Foley, 2001;Katsiyannis, Ryan, Zhang, & Spann, 2008;Meltzer, Levine, Karniski, Palfrey, & Clarke, 1984, Zamora, 2005. For example, in a review of the academic characteristics of juvenile delinquents, Foley (2001) reported that these youth were one year to several years below expected grade levels and had high rates of academic failure and grade retention.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a review of the academic characteristics of juvenile delinquents, Foley (2001) reported that these youth were one year to several years below expected grade levels and had high rates of academic failure and grade retention. Some studies have also found that the majority of juvenile delinquents held in detention centers read at an elementary school level despite an average age of approximately 15 years (Beebe & Mueller, 1993;Meltzer et al, 1984). In one study, Zamora (2005) used the Kaufman Test of Educational Achievement (KTEA) to determine the academic level of 327 delinquent males ages 10 to 17 years.…”
Section: Introductionmentioning
confidence: 99%
“…When comparing these measures to grades 6-9, there was an increase to 66% of delinquents exhibiting a reading delay and a decrease in the comparison group of only 12% of students experiencing difficulties. Furthermore, these other educational factors revealed similar findings of an increase in deficiency prevalence (Meltzer et al, 1984). Not only has a relationship been revealed between juvenile delinquency and a lack of education, but educational problems may go even deeper to include learning disabilities.…”
Section: Educational Factorssupporting
confidence: 57%
“…This academic deficiency typically expands to encompass an array of educational skills. Meltzer et al (1984), in an examination of 53 delinquent adolescent learning profiles, observed, when compared to 51 average junior high school students, delinquents were inadequate in areas such as reading accuracy and comprehension rates, spelling, mathematics, and written expression. Educational dysfunction in juvenile delinquents was identified in the early stages of school, even before the second grade.…”
Section: Educational Factorsmentioning
confidence: 99%
See 1 more Smart Citation